Grants for irrigation of coffee crops in Rondônia – Southern Amazon, from 2010 to 2019 - Santos, Osmair Oliveira dos; Goveia, Grasiela Rocha Torres; Cararo, Denis Cesar; Zuffo, Catia Eliza (Seven Editora, 2024)
The objective of this research is to present a survey of the scenario from 2010 to 2019 regarding the granting of rights to use water for irrigation purposes in coffee farming in the state of Rondônia located in the Southern Brazilian Amazon, to make information available to resource managers water resources for strategic decision-making purposes. For this purpose, bibliographic and documentary information was used, seeking to obtain reliable answers, since irrigation has direct impacts on the water resources available in river basins throughout the state. It is expected to provide managers of this resource with quality in planning actions in a decentralized manner, ensuring the development of economic activities, in a manner compatible with the multiple and environmentally sustainable use of water resources. DOI:https://doi.org/10.56238/sevened2023.006-100